Dual‐Cascade Activatable Nanopotentiators Reshaping Adenosine Metabolism for Sono‐Chemodynamic‐Immunotherapy of Deep Tumors. Issue 10 (2nd February 2023) - Zhan, Meixiao; Wang, Fengshuo; Liu, Yao; Zhou, Jianhui; Zhao, Wei; Lu, Ligong; Li, Jingchao; He, Xu
Abstract: Immunotherapy is an attractive treatment strategy for cancer, while its efficiency and safety need to be improved. A dual‐cascade activatable nanopotentiator for sonodynamic therapy (SDT) and chemodynamic therapy (CDT)‐cooperated immunotherapy of deep tumors via reshaping adenosine metabolism is herein reported. This nanopotentiator (NPMCA ) is constructed through crosslinking adenosine deaminase (ADA) with chlorin e6 (Ce6)‐conjugated manganese dioxide (MnO2 ) nanoparticles via a reactive oxygen species (ROS)‐cleavable linker. In the tumor microenvironment with ultrasound (US) irradiation, NPMCA mediates CDT and SDT concurrently in deep tumors covered with 2‐cm tissues to produce abundant ROS, which results in dual‐cascade scissoring of ROS‐cleavable linkers to activate ADA within NCMCA to block adenosine metabolism. Moreover, immunogenic cell death (ICD) of dying tumor cells and upregulation of the stimulator of interferon genes (STING) is triggered by the generated ROS and Mn 2+ from NPMCA, respectively, leading to activation of antitumor immune response. The potency of immune response is further reinforced by reducing the accumulation of adenosine in tumor microenvironment by the activated ADA. As a result, NPMCA enables CDT and SDT‐cooperated immunotherapy, showing an obviously improved therapeutic efficacy to inhibit the growths of bilateral tumors, in which the primary tumors are covered with 2‐cm tissues. Abstract : An ultrasound and tumor microenvironment dual‐cascade activatable nanopotentiator is constructed for sono‐chemodynamic‐immunotherapy of deep tumors. The nanopotentiator produces abundant reactive oxygen species for inducing immunogenic cell death and activating adenosine deaminase to reshape the adenosine metabolism. Thus, the antitumor immune response is obviously amplified by sono‐chemodynamic‐cooperated immunotherapy to effectively treat deep 4T1 tumors covered with 2‐cm tissues.